A survey of case studies in production scheduling: Analysis and perspectives - Fuchigami, Helio Yochihiro [UNESP]; Rangel, Socorro [UNESP] (Elsevier, 2018)
The problems of production scheduling and sequencing refer to decision making regarding the designation of jobs to available resources and their subsequent order to optimize pre-defined performance measures. From the early days of research in this area until this last decade, the publication of case studies has been scarce, with their frequency only increasing very recently. This survey aims to highlight practical research and case studies published in the literature in the scheduling area, identifying the main characteristics of the problems treated, trends in this research and also gaps showing potential areas for future study.
Keywords: Case studies; Operational research; Production scheduling; Production sequencing